Development and applications of radioactive nanoparticles for imaging of biological systems. (4th September 2014) - Lewis, Michael R.; Kannan, Raghuraman
<x xml:space="preserve">Abstract</x> Radioactive nanoparticles possess the ability to carry high payloads of radionuclides for noninvasive imaging of regions of interest inside the body. In this way, they can be used for nuclear imaging of systems such as normal physiology and disease states. Various methods have been developed to label nanoparticles using both radiometals and radiohalogens, for single‐photon emission computed tomography (SPECT) or positron emission tomography (PET) imaging in laboratory animals. The use of imaging to develop radioactive nanoparticles with long circulation times and minimal reticuloendothelial uptakes led to the design of nanoparticle constructs for imaging animal models of chronic illnesses, such as cancer and cardiovascular disease. Further improvements in targeting were made by modifying these constructs with vectors having high affinity and specificity for diseased tissue. In addition, constructs containing more than one type of imaging material afforded nanoparticles with multimodal properties, such as those designed for nuclear, magnetic resonance, and/or optical detection. Given the close relationship between diagnosis and therapy, theranostic nanoparticles have also been developed both to deliver radiotherapy and monitor response by imaging. In this article, we review the use of radionuclides to label nanoparticles for development and applications involving noninvasive detection of normal and abnormal biological functions. WIREs Nanomed Nanobiotechnol 2014, 6:628–640. doi: 10.1002/wnan.1292 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.